1994
DOI: 10.1093/eurheartj/15.suppl_c.78
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of Insulin Resistance in Hypertension

Abstract: Primary hypertension is a frequent polygenic disease with strong genetic and environmental components. During the last decade, evidence has been increasing that insulin resistance as a marker of increased risk for Type 2 diabetes and cardiovascular atherosclerotic disease is present not only in individuals with obesity, Type 2 diabetes and impaired glucose tolerance, but also in the majority of the hypertensive population. Insulin resistance describes a tissue- and pathway-specific defect of glucose metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…It has been suggested that the common denominators of all these conditions are a defective insulin-stimulated glucose uptake, insulin-resistance and hyperinsulinaemia [12][13][14]. Thus, the most important finding of the present report is that BPH is also an insulin-resistant condition, with secondary hyperinsulinaemia as a possible aetiological factor for BPH.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It has been suggested that the common denominators of all these conditions are a defective insulin-stimulated glucose uptake, insulin-resistance and hyperinsulinaemia [12][13][14]. Thus, the most important finding of the present report is that BPH is also an insulin-resistant condition, with secondary hyperinsulinaemia as a possible aetiological factor for BPH.…”
Section: Discussionsupporting
confidence: 57%
“…Moreover, men with faster BPH growth rates would be more obese, have higher blood pressure, lower HDL cholesterol levels and higher fasting plasma insulin levels than men with slower BPH growth rates. The reason for this is that patients with NIDDM, hypertension, obesity and low HDL cholesterol levels have been shown to have increased fasting plasma insulin levels [12][13][14]. Thus, in the present study, we tested the hypothesis of a causal relationship between high insulin levels and the development of BPH.…”
Section: Introductionmentioning
confidence: 93%
“…The principal pathophysiology of MS is secondary hyperinsulinemia caused by tissue insulin resistance, which stimulates the autonomic nervous system, especially the sympathetic nerve system, thus resulting in bladder outlet obstruction [10,11]. Generally, metabolic components in adult males are highly prevalent, and the prevalence increases with increasing age.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have also suggested that fast-growing BPH is a component of the metabolic syndrome and that patients with fast-growing BPH might share the same metabolic abnormality of a defective insulin-mediated glucose uptake and a secondary hyperinsulinaemia as patients with the metabolic syndrome. This syndrome has been described as a single entity characterized by a defect in the insulin-mediated glucose uptake (19)(20)(21). The primary metabolic abnormality of the metabolic syndrome is mainly localized to the muscle, the adipose tissue and the liver of the patients suffering from this syndrome, leading to insulin-resistance and secondary hyperinsulinaemia (22).…”
Section: Discussionmentioning
confidence: 99%